Results of organ-preserving treatment of breast cancer using intraoperative radial therapy - I. S. Chumachenko; R. A. Murashko; A. A. Keshabyan; P. V. Krivorotko; S. N. Novikov (Опухоли женской репродуктивной системы, 2021)
Objective: to compare the immediate and long-term outcomes of patients with early breast cancer treated with intraoperative radial therapy depending on the biological subtype of breast cancer.Materials and methods. We prospectively evaluated number of recurrences, cosmetic effect and early treatment results of 104 patients with early breast cancer aged 66.72 ± 0.68 years old. The mean follow-up period was 36 months. The mean dose on the surface of applicator was 17.8 Gy, on the depth 0.5 cm – 8.8 Gy, on the depth 1.0 cm – 5 Gy. The mean time of radiation was 22.15 min ± 28.09 sec.Results. The local recurrence was in 3 patients. The first patient had triple negative breast cancer subtype, the second patient had luminal B HER2+, and the third one had luminal B HER2– subtype. Relapses occurred in 7, 14 and 20 months after the end of treatment respectively. The recurrence rate in patients with luminal B biological subtype was 10.71 %; in patients with triple negative subtype was 20 %. All recurrences were found in the area of the postoperative scar.Conclusion. The obtained results question the rationale for the use of the demonstrated method in patients with luminal B and triple negative molecular subtypes of tumors.